Differential Diagnosis, Clinical Characteristics, and Interventions of Braid-Like Coronary Artery: Case Series Analysis Based on Optical Coherence Tomography. (28th October 2020) - Leng, Wen-Xiu; Wang, Huan-Huan; Liu, Hai Ming; Song, Ying; Xu, Lian-Jun; Xu, Jing-Jing; Zhao, Xue-Yan; Tan, Xiao-Yan; Li, Rong; Gao, Zhan; Gao, Li-Jian; Chen, Jue; et al.
Abstract : Aim . Based on optical coherence tomography (OCT), we aimed to determine the diagnosis, clinical characteristics, and interventions of braid-like coronary arteries, which are rare and tend to be diagnosed as a woven coronary artery (WCA) anomaly. Methods and Results . We identified braid-like lesions on coronary angiography (CAG) in 7 patients (6 men; median age 47 years; age range 26 to 57 years). All patients were heavy smokers. Four patients were diagnosed with an old myocardial infarction and the other 3 with unstable angina. The braid-like lesions were located in the left anterior descending arteries in 2 patients and in the right coronary arteries in the other 5. TIMI grade 2 flow was observed in all involved vessels. OCT findings of all lesions were consistent with recanalization of organized thrombi, which consisted of septa that divided the lumen into multiple small cavities communicating with each other. No separate three-layered structure could be defined. Based on the significance of the stenosis and its related symptoms, drug-eluting stents were implanted in all of the lesions. All patients experienced symptomatic improvement after the intervention and were followed up event-free for 12 months. Conclusions . Braid-like coronary arteries are likely to undergo recanalization of organized thrombi rather than WCA according to our OCT findings. The majority of cases affect men who smoke heavily. Percutaneous stent implantation may be beneficial in selected patients when feasible.